O processo de criação de objetos autorreferenciais: memória, bricolagem e narrativa - Corrêa, Mariana Resende (2013)
The Process of Creating self-referential Objects: Memory, Bricolage and Narrative is a research in Visual Poetics that uses objects that had been already used and does not belong to me (except for one), to turn them into self-referential objects. Whereas we are permeated by otherness, it s acceptable the reflective construction of narratives in other objects as a way of creating identity through the otherness presented in objects. With the adoption of used and rejected objects, I studied the proposal of bricolage and bricoleur conceptualized by Claude Lévi-Strauss, that allowed me to extend the past presented in my material memories to those used objects. This series consists of six works whose foundations are three chairs, a stool, a small table and a shelf. From these works I reflect on the different operating processes understood as the own process of bricolage, which involves the composition of an archive formed by objects and fragments of furniture, the criteria for selecting objects that became the artworks basis, the different combinatorial possibilities of different objects and fragments, and interventions on them. In this study, I weave considerations on the concepts of memory brought, mainly, by Maurice Halbwachs, as reconstructing the past from images and ideas we have at the present, and on the concept of narration by Walter Benjamin, as well as the reflection on the autobiography as a space for the expression of modern individuals and this as a kind of narration today. These reflections and discussions were, in turn, developed from references and comparisons to some artworks of artists like: Joseph Cornell, Courtney Smith, Farnese de Andrade, Amanda Mei and Nino Cais.